Composition of ground granulated blast-furnace slag and fly ash-based geopolymer activated by sodium silicate and sodium hydroxide solution: multi-response optimization using Response Surface Methodology - Hoang-Quan Dinh; Thanh-Bang Nguyen (Vietnam Journal of Science, Technology and Engineering, 2021)
Geopolymers are a class of new binder manufactured by activating aluminosilicate source materials in a highly alkaline medium. This binder is considered “environmentally friendly” due to the recycling of industrial waste sources such as fly ash and blast furnace slag. However, in order to be widely used, this binder has to ensure both quality and economic efficiency. This paper focuses on the optimization of the composition of ground granulated blast-furnace slag and fly ash-based geopolymers activated by sodium silicate and sodium hydroxide solutions. Statistical models are developed to predict the compressive strength and cost of 1 ton of binder using Response Surface Methodology (RSM). In this regard, the effects of three principal variables (%Na2O, Ms and %GGBS) were investigated in which: %Na2O - mass ratio of Na2O in the alkali-activated solution and total solids; Ms - mass ratio of SiO2 and Na2O in the activated solution; %GGBS - mass ratio of ground granulated blast-furnace slag (GGBS), and total binder. Quadratic models were proposed to correlate the independent variables for the 28-d compressive strength and cost of 1 ton of binder by using the Central Composite Design (CCD) method. The study reveals that Ms has a minor effect on the strength of mortar in comparison with %Na2O and %GGBS. The optimized mixture proportions were assessed using the multi-objective optimization technique. The optimal values found were %Na 2O=5.18%, Ms=1.16, and %GGBS=50%, with the goals of maximum compressive strength, the largest amount of fly ash, and reasonable cost for one ton of binder. The experimental results show that the compressive strength of the samples ranged between 62.95-63.54 MPa and were consistent with the optimized results (the variation between the predicted and the experimental results was obtained less than 5%).